CONSUMER CREDITING IN RUSSIA AND FINANCE COMPETENCE OF THE POPULATION: CHALLENGES AND PROSPECTS OF DEVELOPMENT - Elena V. Altukhova (Вестник Российского экономического университета имени Г. В. Плеханова)
The present situation in customer crediting in Russia causes a lot of questions and criticism. According to experts the growth in population over-crediting could result in deteriorating the quality of credit service and increase in delays and it can in its turn affect the general economic status. The resolution of this problem is hidden in the system character of its realization. In present conditions we need a well-balanced system of credit relations’ regulation. First of all it deals with strict regulation of the system of micro-financing with simultaneous improving the level of population finance competence. The author shows that these issues’ settlement lies in the field of bank regulation and supervision and in introduction of the institution of customer consulting.